2021
DOI: 10.5223/pghn.2021.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Clinical Application of Next-Generation Sequencing

Abstract: Next-generation sequencing (NGS) technologies have changed the process of genetic diagnosis from a gene-by-gene approach to syndrome-based diagnostic gene panel sequencing (DPS), diagnostic exome sequencing (DES), and diagnostic genome sequencing (DGS). A priori information on the causative genes that might underlie a genetic condition is a prerequisite for genetic diagnosis before conducting clinical NGS tests. Theoretically, DPS, DES, and DGS do not require any information on specific candidate genes. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The overall diagnostic yield of genetic variants identi ed by WES in cohorts of different pathologies varies in the literature from 5% [67], 25,2% [68] to 40 -50% [69, 70], even considering patients with immunological impairment [16,17,71]. From a genetic point of view, these yield variations can be explained, for example, by possible repeated expansion variants, somatic variants and deep intron variants with indeterminate splicing effects [70].…”
Section: Discussionmentioning
confidence: 99%
“…The overall diagnostic yield of genetic variants identi ed by WES in cohorts of different pathologies varies in the literature from 5% [67], 25,2% [68] to 40 -50% [69, 70], even considering patients with immunological impairment [16,17,71]. From a genetic point of view, these yield variations can be explained, for example, by possible repeated expansion variants, somatic variants and deep intron variants with indeterminate splicing effects [70].…”
Section: Discussionmentioning
confidence: 99%
“…2 As of 2016, some papers showed that over 700 genes were reported in syndromic and non-syndromic ID. 1 Ghandil et al reported a novel homozygous variant in an Iranian family with syndromic ID. 3 Therefore, NGS has increased the number of causative genes liked to ID facilitating in the diagnosis of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have accelerated the identification of causative genes and variants involved in the ethology of disease. 1 ID is a heterogeneous neurodevelopmental disorder characterized by significant impairment in intellectual and adaptive functioning with onset during the developmental period. By a total prevalence of 1%–3%, the disease has extensive phenotypic variability and genetic heterogeneity worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The searching of genetic causative variants is mainly entrusted to Sanger sequencing or qPCR systems, where the exon-by-exon or variant-by-variant approach slows down diagnostic times. Fortunately, the advent of next-generation sequencing (NGS) is revolutionizing the field of both diagnosis and screening, playing a relevant role as a genetic support tool in the diagnosis of LSDs always in combination with biochemical and clinical data [ 11 ]. With NGS, the simultaneous analysis of large numbers of genetic loci and samples can drive down costs and turnaround time; laboratory processes can largely be automated, and a single assay can be used to screen a set of disorders (regardless of whether a biochemical marker is available) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%